PENGARUH KONSENTRASI CUKA BAMBU DAN MACAM VARIETAS TERHADAP PERTUMBUHAN STEK LADA PERDU (Piper nigrum L.) - Endang Suliswati; Tri Suwarni Wahyudiningsih; Siti Nurul Iftitah (Universitas Wahid Hasyim, 2020)
The purpose of this study is to determine the effect of concentration of petung bamboo vinegar, kinds of varieties, and the interaction of both on the growth of shrub pepper cuttings. The study used a factorial Randomized Complete Block Design (RCBD) with three blocks. The first factor is the concentration of petung bamboo vinegar (Dendrocalamus asper) consisting of 0 ppm, 1.000 ppm, 2.000 ppm, 3.000 ppm, 4.000 ppm, 5.000 ppm, and 1.000 ppm Indole Acetic Acid (IAA) as a synthetic growth regulator. The second factor is kinds of varieties: Natar-1 and Ciinten. The results showed that the use of petung bamboo vinegar for 5.000 ppm produces the highest number of leaves, fresh weight of shoots, and dry weight of shoots on Ciinten variety, while the Natar-1 variety with concentration of petung bamboo vinegar for 3.000 ppm obtained the highest fresh weight of shoots and dry weight of shoots. Ciinten variety obtained the highest results on shoot height, number of leaves, longest root length, number of roots, fresh weigh of shoots, dry weight of shoots, fresh weight of roots, and dry weight of roots. The interaction between the concentration of petung bamboo vinegar and kinds of varieties has no significant on all observed parameters. The use of petung bamboo vinegar at 3.000 ppm for Natar-1 and 5.000 ppm for Ciinten can replace the role of IAA growth regulator at concentrations of 1.000 ppm. Keywords: Dendrocalamus asper, bamboo vinegar concentration, Piper nigrum L., shrubs pepper cuttings, varieties.